2010
DOI: 10.1590/s1519-69842010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Time and seasonal patterns of activity of phyllostomid in fragments of a stational semidecidual forest from the Upper Paraná River, Southern Brazil

Abstract: Bats may exhibit different patterns of activity, considering aspects concerning niche dynamics as well as the establishment and permanence of the communities in the ecosystems. In this way, the present study analyzed the time and seasonal patterns of activity in different species of frequent phyllostomid bats in remnants of the stational semidecidual forest from the Upper Paraná River, Southern Brazil. Captures were performed between January and December, 2006, using 32 mist nets set above the soil along the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
3
14
0
1
Order By: Relevance
“…Bernard (2002), in a study on continuous forest in the Amazon, obtained similar results for the frugivorous species, but also registered two peaks of activity for Carollia, one at 19:00 and another at 01:00. The same pattern was observed by Ortêncio-Filho et al For large frugivorous, as Artibeus lituratus and A. planirostris, we observed a peak of activity in the three hours after sunset (19:00 and 20:00 respectively) and an increase of activity near dawn, corresponding to the results found in other forest fragments by Aguiar & MarinhoFilho (2004) and Ortêncio-Filho et al (2010). In studies conducted in continuous forest, Bernard (2002) observed a bimodal pattern for A. planirostris, which probably is a common feature of the species in continental regions.…”
Section: Discussionsupporting
confidence: 92%
“…Bernard (2002), in a study on continuous forest in the Amazon, obtained similar results for the frugivorous species, but also registered two peaks of activity for Carollia, one at 19:00 and another at 01:00. The same pattern was observed by Ortêncio-Filho et al For large frugivorous, as Artibeus lituratus and A. planirostris, we observed a peak of activity in the three hours after sunset (19:00 and 20:00 respectively) and an increase of activity near dawn, corresponding to the results found in other forest fragments by Aguiar & MarinhoFilho (2004) and Ortêncio-Filho et al (2010). In studies conducted in continuous forest, Bernard (2002) observed a bimodal pattern for A. planirostris, which probably is a common feature of the species in continental regions.…”
Section: Discussionsupporting
confidence: 92%
“…Both Artibeus had similar patterns of activity at the end of the night; a similar overlap has been reported by Ortencio Filho et al (2010). In Amazonia, Artibeus lituratus also had its activity peak before dawn; however it did not overlap with other Artibeus species.…”
Section: Discussionsupporting
confidence: 82%
“…This is a well known pattern in bat ecology in the Neotropical region (Marinho-Filho and Sazima 1989, Bernard 2002, Aguiar and Marinho-Filho 2004, Ortencio Filho et al 2010. High activity before sunrise is common among Neotropical bats (Brown 1968).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This fact was evidenced for bat assemblages from the Amazonian forest (Bobrowiec et al 2014) and from Atlantic Rainforest (Ribeiro-Mello 2009, Ortêncio-Filho et al 2010, Stevens & Amarilla-Stevens 2012, Stevens 2013, Lourenço et al 2014. For cave bats from Atlantic Rainforest in the Alto Ribeira region, São Paulo state, Trajano (1985) and Arnone (2008) suggested the existence of seasonality, at least for some species.…”
Section: Introductionmentioning
confidence: 90%